Increasing Adolescent Immunization Rates in Primary Care: Strategies Physicians Use and Would Consider Implementing. (August 2013) - Humiston, Sharon G.; Serwint, Janet R.; Szilagyi, Peter G.; Vincelli, Phyllis A.; Dhepyasuwan, Nui; Rand, Cynthia M.; Schaffer, Stanley J.; Blumkin, Aaron K.; Curtis, C. Robinette
Strategies to increase adolescent immunization rates have been suggested, but little is documented about which strategies clinicians actually use or would consider. In spring 2010, we surveyed primary care physicians from 2 practice-based research networks (PBRNs): Greater Rochester PBRN (GR-PBRN) and national pediatric COntinuity Research NETwork (CORNET). Network clinicians received mailed or online surveys (response rate 76%, n = 148). The GR-PBRN patient population (51% suburban, 33% rural, and 16% urban) differed from that served by CORNET (85% urban). For nonseasonal vaccines recommended for adolescents, many GR-PBRN and CORNET practices reported using nurse prompts to providers at preventive visits (61% and 52%, respectively), physician education (53% and 53%), and scheduled vaccine-only visits (91% and 82%). Strategies not used that clinicians frequently indicated they would consider included patient reminder/recall and prompts to providers via nurses or electronic health records. As preventive visits and immunization recommendations grow more complex, using technology to support immunization delivery to adolescents might be effective.